Clinical Comparison of a Newly Developed Ionic Toothbrush with Soft Rubber Filaments and a Manual Toothbrush in Plaque Reduction: A Crossover Clinical Trial - Ryo, MIKAMI; Yumine, KIUCHI; Akane, OCHIAI; Kohei, TAKEDA; Takanori, IWATA; Yuichi, IKEDA; Koji, MIZUTANI; Munehiro, OKADA; Yuichi, IZUMI; Takahiro, IKAWA; Takeaki, SUDO (The Japanese Journal of Conservative Dentistry, 2021)
Purpose: Plaque control is the most important factor for preventing and treating periodontal disease. This study aimed to evaluate the plaque removal efficacy of a newly developed ionic toothbrush with soft rubber filaments as compared to that of a conventional manual toothbrush. Methods: Ionic or manual toothbrushes were randomly assigned to 30 healthy volunteers divided into two groups (Phase Ⅰ). After 2 min of brushing, all the tooth surfaces were stained with a plaque staining solution. Blinded examiners evaluated the remaining plaque using the Rustogi Modified Navy Plaque Index. As representative teeth, the plaque removal rate was calculated at the central incisors, first premolar, and first molar in the maxilla and mandible. As a crossover design, the same examinations using another toothbrush (Phase Ⅱ) were performed for all the subjects 1 week after Phase Ⅰ. A questionnaire survey was conducted to evaluate the patient-reported outcome measures. Results: Ionic toothbrushes were able to achieve a significantly higher plaque removal rate than control toothbrushes in the incisor and first premolar areas (p<0.05). No significant difference was observed in the first molar area. Compared to manual toothbrushes, the newly developed ionic toothbrushes were significantly more efficient, “refreshing”, “easy”, “comfortable”, and “giving slippery feeling” according to the answers provided in the questionnaire survey. Conclusion: Compared to manual toothbrushes, the newly developed ionic toothbrushes with soft rubber filaments were significantly more efficient in removing plaque from the incisor and first premolar areas.